Keefektifan Metode Resitasi dengan Media Pembelajaran Moeko (Monopoli Ekosistem) untuk Meningkatkan Hasil Belajar Siswa di Sekolah Dasar - Diah Fitri Handayani; Joko Siswanto; Sukamto Sukamto (STKIP Andi Matappa Pangkep, 2022)
The purpose of this study was to determine the effectiveness of the recitation method with moeko learning media (ecosystem monopoly) to improve student learning outcomes in elementary schools. This type of research is quantitative research using Pre-Experimental Design (non-design) research with one-group pretest posttest design. The results of the data analysis of students' pretest learning outcomes showed that they obtained an average of 60. While the posttest results obtained an average of 80, then the test was carried out with a comparative test. Then from the t-test, obtained > which is 2,755 > 1,997 so that is rejected and is accepted, meaning that the students' posttest results are better than the students' pretest results. Student learning outcomes achieved the criteria for mastery learning through the pretest score of 8 students 24% had achieved the criteria for completeness and posttest as many as 25 students 88% had achieved the criteria for completeness.